(untitled) (Plant Tissue Culture and Biotechnology, 2019)
Attempt was made to isolate and identify poly-β-hydroxybutyrate (PHB) producing bacteria from different domestic and industrial waste materials from in and around Dhaka Metropolitan city. The bacterial load of the collected samples ranged in between 5.50 ×103 and 2.52 × 107, 3.10 × 104 and 2.23 × 107, 7.50 × 103 and 1.01 × 107 cfu/g or cfu/ml in NAG (nutrient agar glucose), PYG and LB media, respectively. The maximum bacterial count (2.52 × 107 cfu/g) was observed in NAG medium from soil sample of BDR market and the lowest bacterial load (5.5 × 103 cfu/ml) was observed in NAG medium from the garments wastewater. The highest number (33) of PHB producing bacteria was found in the kitchen waste soil and the lowest number (9) was in water sample of the Turag river. All the Sudan Black B positives isolates were tested for positive PHB production. Primarily, 160 PHB positive bacteria were isolated and finally 30 isolates were selected for identification. Provisionally identified potential 10 PHB positive bacterial isolates were identified on molecular basis. Nine of them were matched with their conventional identification but conventionally identified Rhizobium leguminosarum was found to be as Sinorhizobium sp. The isolated PHB producing bacteria could be used for biotechnological application. Plant Tissue Cult. & Biotech. 29(1): 15-24, 2019 (June)